Utilização do barbatimão (Stryphnodendron adstringens) como planta medicinal: uma revisão sistemática - Costa, Lauriane de Lourenço Loures (2021)
Since the dawn of humanity, valid herbal plants have been used to combat various diseases and to treat infectious processes. Among these plants, barbatimão (Stryphnodendron adstringens) has ethnopharmacological potential that is directly related to the levels of condensed tannins present in its metabolism. The objective of the present work was to develop a systematic review about the pharmacological and phytotherapeutic potential of barbatimão (Stryphnodendron adstringens), emphasizing as main purposes of its use and forms of manipulation and ingestion by the Brazilian population. A bibliographic survey was carried out in the SCOPUS database, with the purpose of systematizing the production of scientific knowledge on the use of barbatimão (Stryphnodendron adstringens) as a medicinal plant. By using the search terms "Stryphnodendron adstringens" OR Barbatimão OR Barbatimão OR Barbatimão Real OR Barbatimão OR Barbatimão Or Barbatimão Or Barbatimão Or "Mimosa barbadetimam" OR "Mimosa barbadetimam" OR "Stryphnodendron barbatimam virginiam Medicinal" AND "Stryphnodendron "Stryphnodendron barbatimam" OR Physician. The search resulted in 86 articles referring to barbatimão. However, only 75 articles mention the use of barbatimão (Stryphnodendron adstringens) as a medicinal and pharmacological plant. All researches were carried out in Brazilian territory, and the main uses for barbatimão were as a healing and antibacterial agent. The stem is the physical part most frequently used in studies, but the leaf, even being used, has the same herbal potentials. Therefore, it was found that there is scientific evidence that the stem and leaf of barbatimão have medicinal properties due to the concentration of phenols and even. Furthermore, even though the stem has greater phenolic properties, the concentration present in the leaf is enough for the human body. Therefore, this study also highlights the importance of using barbatimão leaves for consumption, in order to conserve this species, preventing plant death. Since the main access to this medicinal plant is through extractivism